Manajemen Perubahan Pada Kemajuan Organisasi - Sari, Mutia; Aslami, Nuri (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Change is something that cannot be avoided by anyone, especially campus organizations. Changes are made to address the crisis that will be faced in the future. In other words, organizational changes are made to make updates where they come from. Change management in an organization is needed to organize strategies in overcoming existing problems or rejection through existing means. The success of an organization will greatly affect the success or failure of the organization. However, change does not always have a positive impact, changes often also have a negative impact. However, with good management will reduce the threat or risk that will occur.